Transcriptomic responses of Perna viridis embryo to Benzo(a)pyrene exposure elucidated by RNA sequencing. (November 2016) - Jiang, Xiu; Qiu, Liguo; Zhao, Hongwei; Song, Qinqin; Zhou, Hailong; Han, Qian; Diao, Xiaoping
Abstract: The green mussel Perna viridis is an ideal biomonitor to evaluate marine environmental pollution. Benzo(a)pyrene (BaP) is a typical polycyclic aromatic hydrocarbon (PAH), which is well known for the mutagenic and carcinogenic characteristics. However, the toxicological effects of BaP on Perna viridis embryo are still unclear. In this study, we investigated the embryo transcriptomic profile of Perna viridis treated with BaP via digital gene expression analysis. A total of 92, 362, 742 reads were produced from two groups (control and BaP exposure) by whole transcriptome sequencing (RNA-Seq). Gene Ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway analysis were used on all genes to determine the biological functions and processes. Genes involved in various molecular pathways of toxicological effects were enriched further. The differential expression genes (DEGs) were related to stress response, infectious disease and innate immunity. Quantitative real-time PCR (qRT-PCR) measured expressional levels of six genes confirmed through the DGE analysis. This study reveals that RNA-seq for transcriptome profiling of P . viridis embryo can better understand the embryo toxic effects of BaP. Furthermore, it also suggests that RNA-seq is a superior tool for generating novel and valuable information for revealing the toxic effects caused by BaP at transcriptional level. Highlights: Transcriptome responses to BaP exposure of Perna viridis embryos were examined. Genes involved in stress, infectious disease and innate immunity were altered. Gene Ontology and Kyoto Encyclopaedia of Genes and Genomes analysis were conducted. Six stress response-related genes were selected for qPCR analysis for validation.